Status Kepemilikan Hak Atas Tanah Adat Marga dalam Kebijakan Penataan Aset Reforma Agraria Di Kabupaten Maluku Tenggara - Saija, Ronald; Letsoin, Fransiscus X. V. R; Akyuwen, Rory Jeff; Radjawane, Pieter (Faculty of Law, Universitas Pattimura, 2020)
Promulgation of Law Number 5 of 1960, brought its own consequences in terms of regulation of agrarian resources, including earth, water, space and natural resources contained therein. The ideals of the law in the realization of the objectives of the national agrarian law are realized in the form of the Agrarian Reform policy which is one of the ideals in the administration of President Joko Widodo. This policy was stated in the Decree of the People's Consultative Assembly of the Republic of Indonesia Number IX / MPR / 2001 concerning Agrarian Reform and Natural Resource Management and followed up with the issuance of Presidential Regulation Number 86 of 2018 concerning Agrarian Reform. The Presidential Regulation regulates the determination of assets in the legalization of agrarian reform land object certificates. However, the problem is that it is feared that disputes and agrarian conflicts will arise in the right of recognition of the existence of communal rights for indigenous and tribal peoples explicitly mentioned in Ministerial Regulation ATR / Ka.BPN Number 10 of 2016, which seems to be no longer recognized by indigenous peoples in Indonesia. This paper is a legal research that uses the method of the statutory approach and conceptual approach that examines the recognition and use of customary land by using the norms contained in legislation. The results of this paper are directed to be able to provide clarity of legalization of customary community land as well as communal rights of indigenous and tribal peoples related to the issuance of Presidential Regulation Number 86 of 2018 which does not expressly state the position of indigenous peoples as the subject of policy arrangement on Agrarian Reform assets, so that the rights owned by marga indigenous and tribal peoples can be fought for.